Transfer knowledge of organic agriculture for healthy horticulture cultivation on the Bengawan Solo River, Central Java - Widyatmani Sih Dewi; Supriyadi Supriyadi; Mujiyo Mujiyo; Desti Dian Amalina; Muhammad Rizky Romadhon (Community Empowerment, 2023)
Organic farming practices are needed to maintain soil fertility and the health of horticultural products on the banks of the Bengawan Solo river in Jangglengan village, Sukoharjo. This community service aims to teach the farming community about organic farming principles and the practice of making liquid organic fertilizer to support healthy horticultural farming on riverbanks in the Jangglengan area. The partner group, the Jangglengan village government, involves 60 farmer representatives. The methods used were focus group discussion, practices for making liquid organic fertilizer, and evaluation. The results of community service activities show that 75% farmers can show good organic waste material for organic fertilizer, and 95% farmers had improved skills and were able to try making fertilizer by themselves. This organic farming socialization is a good start toward implementing good agricultural practices on the land along the Bengawan Solo River in Jangglengan.